Partizanski filmi in partizanarice - Stanković, Peter (Teorija in praksa, 2012)
Films about partisan struggle against foreign occupation during WW II were made during the entire period of socialist Yugoslavia (1945-1989). Since this period was relatively long and political as well as aesthetic frameworks often changed in those decades, there are not only numerous Yugoslavian partisan films, but they are also extremely diverse. Accordingly, can one talk about Yugoslavian partisan film as a stable film genre at all? After a historical overview of the key developments in the history of Yugoslavian films, the author argues that these films are actually too diverse to be understood as a film genre in any meaningful sense of the word. The only thing that is common to them is their topic, partisan resistance to the foreign occupation, but besides that there is nothing that connects them into any stylistically or even ideologically meaningful whole. Having said that, he proceeds by arguing that within this large and stylistically unspecified framework of Yugoslavian partisan film there is one important segment which can nevertheless be understood as a genre. More specifically, he refers to the set films made during the 1970s as part of the ideological 'normalisation' following Tito's clampdown on nationalist elites. The author defines them as 'partisan westerns' and employs the structuralist method developed by Will Wright to identify their stable narrative and stylistic elements.
Keywords: Film; Filmske zvrsti; Film genres; Partizani; Jugoslavija; Partisans; Yugoslavia; jugoslovanski film; filmski žanri; partizanski film